The influence of intellectual capital on banking financial performance - Kumala, Lela Kori; Hariyanti, Widi; Siddiq, Faiz Rahman (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
This study aims to examine the influence of Intellectual Capital on financial performance. Based on the model proposed by Pulic, the measurement of intellectual capital can use Value Added Intellectual Capital (VAICTM) consisting of Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE) and Structural Capital Efficiency (SCE). This study uses 2 research variables, namely the dependent variable consisting of Return on Assets (ROA) as an indicator of the company's financial performance and the independent variable consisting of HCE, CEE, SCE and VAIC. The analysis data in this study used 2 types of analysis, namely the VAIC simple linear regression test and multiple linear regression to test the VAIC component. The results showed that CEE and HCE had a positive and significant effect on the company's financial performance, and VAIC had a positive and significant effect on the company's financial performance. Meanwhile, SCE has no effect on the company's financial performance.